UPAYA MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK USIA DINI MELALUI AKTIVITAS BERMAIN MAZE DI KELOMPOK A RA AL-GOZALI BANDUNG - Shabila Rahmalia Rahayu; Teti Ratnasih; Nano Nurdiansah (Azzahra: Jurnal Pendidikan Anak Usia Dini, 2022)
Based on preliminary studies, there are several problems at RA Al-Gozali Bandung related to children’s cognitive development abilities that have not developed optimally. These problems include children not being able to create something according to their own ideas related to various problem solving, classifying objects into the same group or groups in pairs with two variations, recognizing number symbols, and recognizing letter symbols. The purpose of this study was to find out: 1) Cognitive development of early childhood in Group A RA Al-Gozali Bandung before the maze playing activity was implemented; 2) The process of implementing maze playing activities to improve early childhood cognitive development in group A RA Al-Gozali Bandung in each cycle; 3) Cognitive development of children after implementing maze playing activities in group A RA Al-Gozali Bandung in each cycle. This study uses a class action research method. Based on the results of data analysis in this study, it is known that the cognitive development of children before the action is carried out obtains an average value of 39.17 with failure criteria. Children’s cognitive development increases in each cycle, namely in cycle I the average value obtained reaches 46.68 with failure criteria and in cycle II the average value obtained increases to 89.80 with very good criteria. Based on the results obtained, it is proven that maze playing activities can improve children’s cognitive development.